Multi-channel cell to irradiate the material specimens by electrons in the interior of the supercritical water convection loop - Bakai, A.S.; Boriskin, V.N.; Bratchenko, M.I.; Gorenko, Yu.V.; Dovbnya, A.N.; Dyuldya, S.V.; Kovalev, G.G. (Вопросы атомной науки и техники, 2015)
The 1.2×1.5 m sized Supercritical Water Convection Loop with four-channel irradiation cell was created in KIPT. The stainless steel made plant opens the possibility to carry out simulation corrosion tests of candidate structural materials for Generation IV Supercritical Water-Cooled Reactors (SCWR) under irradiation. Specimens in water flow at 350…400°C, 23…25 MPa are irradiated by 10 MeV/10 kW electron beam of LPE-10 linear accelerator. The results of the four-channel cell application for 500 hours long irradiation Zr and Inconel samples are presented. У ХФТІ створена суперкритична водяна конвекційна петля з чотирьохканальною камерою опромінення. Петля розміром 1,2×1,5 м виготовлена з нержавіючої сталі. Установка дозволяє проводити корозійні тести кандидатних конструкційних матеріалів реакторів IV покоління з надкритичним водяним охолодженням під опроміненням. Зразки в потоці води при 350…400 °C, 23…25 МПа опромінюються електронним пучком 10 МеВ/10 кВт лінійного прискорювача ЛПЕ-10. Наведено результати використання чотирьохканальної камери під час 500-годинного сеансу опромінення зразків цирконію та інконелю. В ХФТИ создана суперкритическая водяная конвекционная петля с четырехканальной камерой облучения. Петля размером 1,2×1,5 м изготовлена из нержавеющей стали. Установка позволяет проводить коррозионные тесты кандидатных конструкционных материалов реакторов IV поколения с сверхкритическим водным охлаждением под облучением. Образцы в потоке воды при 350…400°C, 23…25 МПа облучаются электронным пучком 10 МэВ/10 кВт линейного ускорителя ЛУЭ-10. Приводятся результаты использования четырехканальной камеры во время 500-часового сеанса облучения образцов циркония и инконеля.